Limitation of war and the pursuit of justice - Shank, Gregory (Social justice, 2001)
Following the September 11, 2001, terrorist attacks on New York and the Pentagon, symbols of global capitalism and militarism, the military hawks were at a loss as to how to respond, other than to declare a generalized “war on terrorism.” The immediate reaction to the attacks on U.S. soil was to increase policing and border enforcement powers, which served to dramatically enhance the ability of investigators to conduct electronic surveillance, detain foreign suspects, and call for more stringent criminal penalties in terrorism cases. The “war” on terrorism can only be won by examining the structural causes of violence—people must manifest a respect for the innocence of civilian life and reinforce that respect with a real commitment to the worldwide promotion of social justice.